Content of macro- and microminerals in wrapped forages for horses - Zhao, Xue (SLU/Dept. of Animal Nutrition and Management (until 231231), 2014)
A study of the macro- and micromineral contents in wrapped forages in Sweden and Norway was conducted. A total of 124 forage samples collected from 124 farms were analyzed for contents of Ca, P, Mg, K, Na, Co, Cu, I, Fe, Mn, Se and Zn. Information regarding forage production management was collected from each farm and included factors such as fertilization, botanical composition, sward age, etc. Mean (standard deviation) concentrations were: Ca, 5.3 (3.41); P, 2.7 (0.80); Mg, 1.8 (0.76); K, 21.7 (7.44); Na, 0.3 (0.45) g/kg dry matter (DM); and Co, 0.09 (0.15); Cu, 4.9 (1.61); I, 0.2 (0.39); Fe, 194 (288); Mn, 85 (49); Se, 0.02 (0.03); Zn, 23 (9.5) mg/kg dry matter (DM). Comparisons with the daily mineral requirements of horses of different categories indicated that most samples had sufficient levels of Mg, K, Fe and Mn while a minority was sufficient in Na, Co, Cu, I, Se, and Zn. The contents of Ca and P were enough to cover requirements of horses at maintenance but borderline to deficient for heavily exercising, gestating, lactating and rapidly growing horses. Thus, supplementation with Ca, P, Na, Co, Cu, I, Se, and Zn minerals is suggested to horses fed only forages. Forage management practices influenced the content of some macro- and microminerals. Contents of several minerals were positively correlated with increasing harvest number and negatively correlated with increasing wilting time.